Genotypic Variation in Nitrogen Utilization Efficiency of Oilseed Rape (Brassica napus) Under Contrasting N Supply in Pot and Field Experiments - He, Huiying; Yang, Rui; Li, Yajun; Ma, Aisheng; Cao, Lanqin; Wu, Xiaoming; Chen, Biyun; Tian, Hui; Gao, Yajun (Frontiers in Plant Science, 2017)
Oilseed rape characteristically has high N uptake efficiency and low N utilization efficiency (NUtE, seed yield/shoot N accumulation). Determining the NUtE phenotype of various genotypes in different growth conditions is a way of finding target traits to improve oilseed rape NUtE. The aim of this study was to compare oilseed rape genotypes grown on contrasting N supply rates in pot and field experiments to investigate the genotypic variations of NUtE and to identify indicators of N efficient genotypes. For 50 oilseed rape genotypes, NUtE, dry matter and N partitioning, morphological characteristics, and the yield components were investigated under high and low N supplies in a greenhouse pot experiment and a field trial. Although the genotype rankings of NUtE were different between the pot experiment and the field trial, some genotypes performed consistently in both two environments. N-responder, N-nonresponder, N-efficient and N-inefficient genotypes were identified from these genotypes with consistent NUtE. The correlations between the pot experiment and the field trial in NUtE were only 0.34 at high N supplies and no significant correlations were found at low N supplies. However, Pearson coefficient correlation (r) and principal component analysis showed NUtE had similar genetic correlations with other traits across the pot and field experiment. Among the yield components, only seeds per silique showed strong and positive correlations with NUtE under varying N supply in both experiments (r=0.47**; 0.49**; 0.47**; 0.54**). At high and low N supply, NUtE was positively correlated with seed yield (r=0.45**; 0.53**; 0.39**; 0.87**), nitrogen harvest index ( r=0.68**; 0.82**; 0.99**; 0.89**), and harvest index (r=0.79**; 0.83**; 0.90**; 0.78**) and negatively correlated with biomass distribution to stem and leaf ( r=-0.34**; -0.45**; -0.37**; 0.62**), all aboveground plant section N concentration (r from-0.30* to -0.80**), N distribution to the vegetative parts (silique husk, stem and leaf) (r from-0.40** to -0.83**). N-efficient (N-responder) genotypes produced more seeds per silique and had significantly higher NHI and HI than did N-inefficient (N-nonresponder) genotypes. In conclusion, across the pot and field experiments, the 50 genotypes had similar underlying traits correlated with NUtE and seeds per silique may be a good indicator of NUtE.